P46 Treatable traits in a severe asthma cohort. (December 2018) - Connolly, C; Borg, C; Gittins, A; Shrimanker, R; Hynes, G; Hinks, T; Pavord, I
Abstract : Introduction and objectives: Asthma is a complex chronic respiratory disease which is characterised by several identifiable and treatable traits. The most clinically impactful being airway inflammation and airflow limitation. Asthma management plans are often impacted by many pulmonary and extra-pulmonary co-morbidities, risk factors and triggers. A multidimensional assessment 1 of 'treatable traits' could be an effective strategy to assess disease heterogeneity in severe asthma, enabling the application of precision medicine to chronic airways disease. 2 We reviewed new referrals to our severe asthma clinic over a 6 week period to evaluate how those approaches can help in the management of our own patients. Methods: We performed a systematic, case-notes review of prospectively-collected data from all consecutive referrals collected over a 6 week period. Results: Over a 6 week period, we reviewed 37 new-patient referrals. The average age was 54 years old, with a male:female ratio of 2:3. From the fourteen traits considered, an average of 3.8 traits per person (range 2 to 10) were identified. The three most dominant traits were found to be atopy (72% of those analysed), anxiety/depression (62.5%), and airflow limitation (59.5%) whereas the three least dominant traits were identified as dysfunctional breathing (3%), smoking (13.9%) and poor inhaler technique (26.9%). Of the dominant traits, 0% of patients were treated for anxiety/depression compared with 50% and 45.5% for atopy and airflow limitation respectively. Conclusions: New referrals to our severe asthma clinic are complex and have a number of comorbid conditions or traits in addition to airflow limitation and airway inflammation. Identification of these is potentially important as they may be driving symptoms which will not be responsive to increased therapy targeting airflow limitation and airway inflammation. Evidence-based interventions targeted at the identified traits are required for a multi-dimensional treatment approach. References: Clark V, Gibson P, Genn G, Pavord I, McDonald V. Multidimensional assessment in severe asthma: A systematic review. European Respiratory Journal 2017;501090. doi:10.1183/1393003.congress-2017.PA1090 Agustí A, Bafadhel M, Beasley R, Bel EH, Faner R, Gibson PG, Louis R, McDonald V, Sterk PJ, Thomas M, Vogelmeier C, Pavord ID. Precision medicine in airway diseases: Moving to clinical practice. European Respiratory Journal 2017;50 (4):1701655. doi:10.1183/13993003.01655–2017